Effect of heat treatment on microstructure and tensile properties of laser deposited titanium alloy TC21. (July 2014) - Zhuo, L.; Changmeng, L.; Dong, L.; Huaming, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Laser deposited titanium alloy TC21 was annealed and aged in the α+β region. The microstructure evolution process and tensile properties were investigated systematically. The annealing temperature mainly influenced the shapes and volume fraction of primary α, while the aging temperature mainly influenced the shapes and volume fraction of secondary α. A unique bi-modal microstructure with coarse crab-like primary α and fine secondary α was observed in the annealing process. The result showed that the crab-like structure appeared in the air cooling process and became more manifest when aging at a somewhat higher temperature. The heat-treated alloy showed good comprehensive tensile properties when annealed at 930°C for 1 h and aged at 600°C for 4 h.